2014
DOI: 10.1074/jbc.m114.562082
|View full text |Cite
|
Sign up to set email alerts
|

Phototransformation of the Red Light Sensor Cyanobacterial Phytochrome 2 from Synechocystis Species Depends on Its Tongue Motifs

Abstract: Background: Phytochromes are bilin-dependent red/far red photoreceptors. Results: Late processes of the P r 3 P fr photoconversion involve large scale conformational changes within the tongue region. Conclusion: Early intermediates lumi-R and R1 affect only the chromophore and its nearest surroundings, whereas late R2 formation recruits the Trp motifs in the peripheral tongue. Significance: The conserved motifs of the tongue region are important for photoconversion and presumably for signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 39 publications
(107 reference statements)
0
30
0
Order By: Relevance
“…We also identified two knotless Phys, Mbl0113 and Mbl3828, which possess distinct domain structures (Table 2) and photochemical properties (Fig. 6) relative to SyCph2, the single knotless Phy in Synechocystis 6803 (48). These studies also expand our knowledge of both the diversity and spectral tuning of dual Cys CBCR GAFs.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We also identified two knotless Phys, Mbl0113 and Mbl3828, which possess distinct domain structures (Table 2) and photochemical properties (Fig. 6) relative to SyCph2, the single knotless Phy in Synechocystis 6803 (48). These studies also expand our knowledge of both the diversity and spectral tuning of dual Cys CBCR GAFs.…”
Section: Discussionmentioning
confidence: 53%
“…4). To gain insight into the chromophore binding pockets and chromophore-protein interactions in these new proteins, we leveraged crystal structures of GAF domains from SyCph1, SyCph2, and a red-absorbing dark state (Pr) of AnPixJg2, and a green-absorbing photoproduct (Pg) of TePixJ (3,47,48). Notably, we chose to use the AnPixJg2 structure (Protein Data Bank code 3W2Z) to map these amino acid residues onto the conserved GAF domain fold that surrounds the PCB chromophore (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hairpin conformational switch, mutational studies on several Phys showed that the hairpin/GAF domain interactions are critical to Phy chemistry despite limited contact with the chromophore. For example, single amino acid substitutions within the PRXSF, WGG, and HbXE motifs either preclude photoconversion of Pr to Pfr, or enhance or stall thermal reversion if the Pfr state was generated, consistent with their predicted ability to impact the hairpin/GAF domain interface as Pr or Pfr (Essen et al, 2008;Anders et al, 2013Anders et al, , 2014Burgie et al, 2014aBurgie et al, , 2014b.…”
Section: Structure Of the Phy Domain And Associated Hairpinmentioning
confidence: 97%
“…Most of the knowledge in molecular phytochrome research was obtained from cyanobacterial phytochromes and bacteriophytochromes which employ phycocyanobilin (PCB) and biliverdin (BV) as chromophores, respectively (Rockwell and Lagarias, 2010 ). These phytochromes are more tractable than plant phytochromes and thus, the first three-dimensional (3D) structures at atomic resolution were obtained from these representatives of the superfamily (Wagner et al, 2005 , 2007 ; Yang et al, 2007 , 2008 , 2009 , 2011 ; Essen et al, 2008 ; Malliet et al, 2011 ; Bellini and Papiz, 2012 ; Anders et al, 2013 , 2014 ; Takala et al, 2014 ). Crystallographic studies of a bacteriophytochrome also revealed the protein structural changes implicated in regulating the output module (Takala et al, 2014 ) that is typically a histidine kinase-like region.…”
Section: Introductionmentioning
confidence: 99%